Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

While trying to represent the poles and analytic continuation of $\Gamma (x)$ , the author uses the following equality:

$$\int\nolimits_{0}^{1}t^{x-1}e^{-t}dt=\sum_{n=0}^{+\infty}\frac{{(-1)}^{n}}{(n+x)n!}.$$ Any help in figuring out how?

share|cite|improve this question
up vote 13 down vote accepted

In order to expand my comment: put for $0\leq t\leq 1$: $\displaystyle S_n(t)=\sum_{k=0}^n\frac{(-t)^k}{k!}$. We have $$\sup_{0\leq t\leq 1}|\exp(-t)-S_n(t)| = \sup_{0\leq t\leq 1}\sum_{k=n+1}^{+\infty}\frac{(-t)^k}{k!}\leq \sum_{k=n+1}^{+\infty}\frac 1{k!},$$ and since the series $\displaystyle\sum_{k=0}^{+\infty}\frac 1{k!}$ is convergent, the sequence $\{S_n\}$ converges uniformly to $t\mapsto \exp (-t)$ on $\left[0,1\right]$. Therefore, we can switch the series and the integral for $x\geq 1$:

$\begin{align*} \int_0^1t^{x-1}e^{-t}dt&=\int_0^1t^{x-1}\left(\sum_{k=0}^{+\infty}\frac{(-1)^kt^k}{k!}\right)dt\\ &=\sum_{k=0}^{+\infty}\frac{(-1)^k}{k!}\int_0^1 t^{x+k-1}dt\\ &=\sum_{k=0}^{+\infty}\frac{(-1)^k}{k!(x+k)}. \end{align*}$

For $0<x<1$, we can use the dominated convergence theorem since $|t^{x-1}S_n(t)|\leq e\cdot t^{x-1}$ which is integrable on $\left[0,1\right]$ (we can use a more simple argument in the case $x\geq 1$).

share|cite|improve this answer

If it does help you please look at this link.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.